Integration of Circular Economy and Sustainable Waste Management as a Best Practice for Sustainable Waste Governance: A Case Study of the PRIMADONA BERDAYA CSR Program of PT Pertamina Patra Niaga IT Balongan - Yhova Muliana; Afiana Muslikhah; Riezqi Fajar; Arfianto Trisnawan; Rahma Laili Khairina (Global Writing Academica Researching and Publishing, 2025)
This study aims to examine how the PRIMADONA BERDAYA Program has successfully integrated the concepts of circular economy and sustainable waste management in fostering sustainable waste governance in Sliyeg Lor Village, Indramayu Regency. The method applied in this research was qualitative descriptive with a case study design. Primary data were collected through participatory observation, in-depth interviews, and Focus Group Discussions (FGDs), while secondary data were obtained from program documentation, corporate CSR reports, relevant literature, and journal articles. The findings reveal that through four innovative subprograms, including Griya Kreasi, SERASA, SITOPANG, and BIONA, the PRIMADONA BERDAYA program has emerged as a best practice in sustainable waste governance. This is reflected in its multidimensional impacts: economic impacts in the form of increased income among millennial farmer groups by 30–40% and the reduction of greenhouse operational costs through the optimization of solar power plants (PLTS) by 100%; environmental impacts including a 10% reduction in household waste and a 100% reduction in company seal waste; social impacts through strengthened cohesion and solidarity, as well as expanded access to environmental education (including primary schools); and sustainability impacts through program replication in Tegalurung Village with strengthened collaboration with educational institutions.